Spinopelvic malalignment correlates to lumbar instability and lumbar musculature in chronic low back pain-an exploratory study - Tahere Seyedhoseinpoor; Mohammad Ali Sanjari; Mohammad Taghipour; Mehdi Dadgoo; Seyed Javad Mousavi (Scientific Reports)
Abstract As PI-LL mismatch is an effective index for spinal surgery and PI-LL less than 10 probably indicates better quality of life, this study aimed to assess spinopelvic parameters, lumbar instability, and lumbar muscle morphology in patients with chronic low back pain (CLBP) with different PI-LL mismatches. This cross-sectional study included 158 CLBP patients. The association between lumbar extensor muscle morphology (measured from magnetic resonance imaging) and spinopelvic parameters (measured from standing lateral radiographs) and lumbar instability (measured from lumbar flexion/extension radiographs) was compared between two groups of patients with different PI-LL mismatch. PI-LL mismatch showed a significant medium association with lumbar spine stability (χ2 = 8.06, p-value = 0.005, OR = 0.26, 95% CI = 0.10 to 0.69). Total cross-sectional area (TCSA) (OR = < 0.001, 95% CI = < 0.001 to < 0.001), functional cross-sectional area (FCSA) (OR = < 0.001, 95% CI = < 0.001 to < 0. 001) of the multifidus, psoas major TCSA (OR = < 0.001, 95% CI = < 0.001 to < 0.001) and its FCSA (OR = < 0.001, 95% CI = < 0.001 to 0.009) showed a strong negative association with PI-LL mismatch. Patients with lower PI-LL mismatch are younger and have less spinopelvic deviation. They have more local spinal compensatory mechanisms such as increased lumbar lordosis. They have better lumbar musculature and less disability but more lumbar instability.